Antarctic scallop (Adamussium colbecki) annual growth rate at Terra Nova Bay - CHIANTORE, MARIACHIARA; R. CATTANEOVIETTI; O. HEILMAYER (Springer Verlag Germany:Tiergartenstrasse 17, D 69121 Heidelberg Germany:011 49 6221 3450, EMAIL: g.braun@springer.de, INTERNET: http://www.springer.de, Fax: 011 49 6221 345229, 2003)
Adamussium colbecki is one of the most wellstudied Antarctic molluscs. However, information on its growth rate is currently based on estimates from mark and recapture experiments and from growth-ring analyses. This paper provides the first estimates of the growth pattern of this scallop throughout a year, for individuals maintained under both natural field and laboratory conditions. Results show size-related differences in growth rate, both in the field and in aquaria, with scallops in Terra Nova Bay growing faster than those kept in aquaria. Growth performances were lower than those reported in the literature